Movement Biomechanics and Injury Prevention in Soccer: A Review of Cutting, Landing, and Deceleration Tasks - Mahmuddin Mahmuddin; Dara Latifah; Sangap Parulian Kaloko; Nasib Septian Sianturi; Aldo Christian (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2026)
The purpose of the study. This systematic review aimed to synthesize current evidence on the biomechanical characteristics of three high-risk movement tasks in soccer—cutting maneuvers, landing mechanics, and deceleration patterns—and to evaluate their roles in the etiology of lower extremity injuries, particularly anterior cruciate ligament (ACL) ruptures, hamstring strains, and ankle sprains. Additionally, the review identified modifiable biomechanical risk factors and examined the effectiveness of injury prevention programs (IPPs) in altering harmful movement patterns across different competitive levels and age groups. Materials and methods. A comprehensive systematic review was conducted in accordance with PRISMA 2020 guidelines. Electronic databases (PubMed/MEDLINE, Scopus, Web of Science, SPORTDiscus, CINAHL, and Cochrane Library) were searched from inception to December 2024. Eligible studies included peer-reviewed research involving soccer players aged ≥13 years, utilizing quantitative biomechanical assessments (e.g., 3D motion capture, force plates, EMG), and reporting outcomes related to injury risk or prevention. Study selection was independently performed by two reviewers, with methodological quality assessed using the Downs and Black checklist and the Cochrane Risk of Bias Tool. A total of 68 studies (n = 4,312 participants) met the inclusion criteria. Results. Findings revealed consistent biomechanical patterns associated with increased injury risk. In cutting tasks, excessive knee valgus (>10°) and reduced hip abductor activation were present in 81% of high-risk cases. Landing analyses showed that stiff landing strategies, characterized by high ground reaction forces (>3.2 body weight) and limited knee flexion (<30°), increased ACL loading by 42–68%. In deceleration tasks, posterior trunk lean, low hamstring-to-quadriceps strength ratios (<0.6), and anterior foot placement relative to the center of mass were dominant risk factors. Injury prevention programs incorporating neuromuscular training, plyometrics, and technique feedback significantly reduced injury incidence (RR = 0.51, 95% CI: 0.38–0.68, p < 0.001). Conclusions. In conclusion, soccer-specific cutting, landing, and deceleration movements are strongly associated with non-contact lower extremity injuries. Targeted neuromuscular training focusing on knee valgus control, improved landing mechanics, and hamstring strengthening is effective in reducing injury risk. Future studies should explore fatigue-related biomechanical changes and enhance early screening strategies.